Clinical Importance of the Persistent Primitive Trigeminal Artery in Vascular Lesions and Its Role in Endovascular Treatment - Wang, Yiheng; Yu, Jinlu (Frontiers in Neurology, 2022)
The persistent primitive trigeminal artery (PPTA) extends from the internal carotid artery to the basilar artery between the origins of the anterior inferior cerebellar artery and superior cerebellar artery. PPTAs have complex anatomical characteristics. Salas and Saltzman classifications are most often used in PPTAs. The PPTA can play many roles in vascular lesions, including intracranial aneurysms, brain arteriovenous malformations, trigeminal artery-cavernous fistulas, Moyamoya disease, and large vessel occlusion. For these lesions, surgical treatment is difficult due to the deep location and complex anatomy of the PPTA, but endovascular treatment (EVT) has emerged as a good alternative. Currently, a complete review of the clinical importance of the PPTA in terms of its role in the development and EVT of vascular lesions is lacking. Therefore, we conducted a PubMed search, performed a review of the relevant extracted literature and cataloged our experience with PPTAs. By review, we found that a thorough understanding of the anatomical and angiographic features of this PPTA is of utmost importance when making therapeutic decisions for any of these pathological conditions.